Pemberdayaan Masyarakat dalam Pembuatan Lulur Tradisional dari Beras dan Kunyit di Kecamatan Cempaka Banjarbaru - Helmina Wati; Rahmi Hidayati; Eny Hastuti; Nurul Mardiati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
As we get older, the skin will undergo an aging process. Aging is caused by a variety of factors both from within and from outside the body. As a traditional raw material, turmeric (Curcuma longa L) contains natural metabolite compounds in the form of curcumin. Rice and turmeric are ingredients often found in the community. The use of rice for beauty is still very little known to the public. The target of this activity is the community of Cempaka Banjarbaru, South Kalimantan. The objective of this activity is to improve the community's skills in making traditional scrubs. The method is to provide training/demonstrations in making scrub preparations. The result of this community service activity is that people can practice making scrubs from turmeric and rice. This activity concludes that the scrub products processed by the community service team can be well received by the residents, which is indicated by the enthusiasm of the residents asking questions and trying the scrub products made.